Role of Pituitary Tumour Transforming Gene 1 in Medullary Thyroid Carcinoma. (2010) - Zatelli, Maria Chiara; Tagliati, Federico; Amodio, Vincenzo; Buratto, Mattia; Pelizzo, Mariarosa; Pansini, Giancarlo; Bondanelli, Marta; Ambrosio, Maria Rosaria; Uberti, Ettore C. degli
Abstract : Background : Pituitary tumour transforming gene 1 ( PTTG1 ) is over-expressed in a variety of endocrine-related tumours. We aimed at evaluating PTTG1 expression and function in human neoplastic parafollicular C-cells, represented by medullary thyroid carcinoma (MTC) and C-cell hyperplasia (CCH) samples and by the TT cell line. Methods : TT cells and tissues derived from human CCH (8 samples) and MTC (12 samples) were analyzed by northern blot, furthermore TT cells were subjected to PTTG gene silencing and cells were analyzed for DNA synthesis. Results : PTTG1 expression was significantly higher ( p < 0.01) in CCH (3-fold), in papillary thyroid cancer and in MTC (5-fold) than in normal thyroid, and in MTC lymph-node metastases as compared to primary lesions (~2-fold; p < 0.05). PTTG1 mRNA and protein correlated with tumour diameter and TNM status (p < 0.05). In TT cells, PTTG1 silencing did not completely block DNA synthesis, but significantly reduced [ 3 H]Thymidine incorporation (~50%; p < 0.01) for up to 3 days. Conclusion : PTTG1 levels correlate with tumour aggressiveness. PTTG1 silencing causes reduced MTC cell proliferation, supporting the hypothesis that PTTG1 might have an important role in C-cell neoplastic proliferation.